2016
DOI: 10.3390/molecules22010013
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Pseudostellariae Radix Based on Simultaneous Determination of Multiple Bioactive Components Combined with Grey Relational Analysis

Abstract: Pseudostellariae Radix (PR) is an important traditional Chinese herbal medicine (TCM) with vast clinical consumption because of its positive effects. However, little attention has been devoted to simultaneous analysis of its bioactive components for quality control of PR based on its different harvesting times, different growing habitats, and different processing methods. In this research, the quality of PR was evaluated based on simultaneous determination of multiple bioactive components combined with grey re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Four groups of fresh AVF harvested under salt treatments were naturally dried, and then powdered and passed through a 60-mesh sieve. 0.3 g of sample was weighed accurately and ultrasonically extracted with 30 mL of water for 45 min, supplemented with water to compensate for the lost weight, and centrifuged at 12000 rpm for 15 min [ 11 , 73 ]. The supernatant was stored at 4 °C and filtered through a 0.22 μm membrane (Jinteng laboratory equipment Co., Ltd., Tianjin, China) before being subjected to UFLC-MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Four groups of fresh AVF harvested under salt treatments were naturally dried, and then powdered and passed through a 60-mesh sieve. 0.3 g of sample was weighed accurately and ultrasonically extracted with 30 mL of water for 45 min, supplemented with water to compensate for the lost weight, and centrifuged at 12000 rpm for 15 min [ 11 , 73 ]. The supernatant was stored at 4 °C and filtered through a 0.22 μm membrane (Jinteng laboratory equipment Co., Ltd., Tianjin, China) before being subjected to UFLC-MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The content of HB was the highest in the Jiangsu P. heterophylla ; however, almost no HB was detected in the Fujian P. heterophylla . Previous studies have also shown that there are obvious differences in the quality of different cultivated P. heterophylla from different fields (Hua et al, 2016b; Hua et al, 2016c). These variances might be related to differences in the ecological environment, genetic information, and cultivation techniques.…”
Section: Discussionmentioning
confidence: 96%
“…Molecular and characteristic fragment ions of 16 chemical components are seen in Table 2. Their structures were investigated through fragmentation reactions of mass spectrum and compared with the existing literature (Fu et al, 2012;Hua et al, 2017 Figure 3. The relative contents in percentage were calculated using the area normalization method, after the ethyl acetate crude extract was purified to remove naturally occurring impurities, which indicated that the cyclic-peptides content in freeze-dried powder was up to 92.94%.…”
Section: Freeze-dried Powder Identification By Uplc-ms/ms Analysismentioning
confidence: 99%